Education and Hospital Chart Related with Anemia among 3 rd Trimester of Pregnant Women - Fatimah Fatimah; Siti Arieska Shomadiyyah (Alma Ata University Press, 2017)
Anemia in pregnancy is a problem serious, especially in Indonesia. This research used quantitative with explanatory research. In the work area of Puskesmas Pajangan from 10 pregnant women, 7 of them experienced anemia. The purpose of this study to determine the relationship between education, history of disease, age and the work of anemic mothers in the third trimester of pregnancy. This research is a quantitative research with explanatory research design. The population was 85 pregnant women in third trimester at Puskesmas Pajangan. The independent variable was characteristics pregnant mothers and dependent variable is anemia in third trimester of pregnancy at Puskesmas Pajangan Yogyakarta. The research uses a questionnaire that has been tested and reliability validity test. Bivariate analysis use was Pearson and Spearman. The results of the analysis bivariate p-value of age mother (0.071), education (0.003), disease history (0.007), work (0.097). In conclusion, there was related between education and disease history with the genesis anemia, While age and job did not relate to anemia in third trimester of pregnancy